موقف القرآن الكريم مع الأديان الأخرى: دراسة تحليلية: The Position of Holy Qur’an with Other Religions: An Analytical Study - Mohamed Mursaleen Mohamed Ismail,; Abdul Sattar Abdul Rahman,; Mohamed Iyaz Abdul Latheef, (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث يهدف هذا البحث إلى تعريف القرآن الكريم والمقصود بالأديان الأخرى كما يتعرض البحث إلى موقف القرآن الكريم تجاه الأديان الأخرى وذلك من خلال نصوص القرآن الكريم والسنة النبوية الشريفة وأقوال السلف الصالح الذين قال فيهم الحبيب صلى الله عليه وسلم "خير أمتي قرني ثم الذين يلونهم ثم الذين يلونهم". يقوم البحث بتسليط الضوء على نماذج تطبيقية التي قام بها الحبيب صلى الله عليه وسلم في عهده وكذا أصحابه رضوان الله تعالى عليهم أجمعين. وبما أن هذا البحث يتعلق بالقرآن الكريم وموقفه مع الأديان الأخرى، فإن المنهج المناسب الذي اعتمد عليه الباحثون هو المنهج الاستقرائي والتحليلي. وقد خلص البحث إلى أن موقف القرآن الكريم كان واضحا صريحا مع الأديان الأخرى على حقيقة الأصل الواحد وهو أن الله تعالى هو الذي خلق جميع البشر من ذكر وأنثى وأن الأفضل والأتقى من الناس هو من اتقى الله عز وجل. كما أن القرآن الكريم قد أشار إشارة صريحة في إعطاء الأديان الأخرى حرية المعتقد والفكر والعبادة بحيث لم يجبرهم على الدخول في الإسلام وهكذا لقد خاطب القرآن الكريم أهل الكتاب بكلمة سواء ونبههم على ما حدث من التحريفات في كتبهم. ABSTRACT This research aims to define the Holy Qur’an and what is meant by other religions. The research also addresses the position of the Holy Qur’an towards other religions, through the texts of the Holy Qur’an, the noble Sunnah of the Prophet, and the sayings of the righteous predecessors, about whom the Beloved Prophet Muhammad (PBUH) said, “The best of my nation is my generation, then those who follow them, then those who follow them.” The research sheds light on the applied models that the Beloved Prophet Muhammad (PBUH) carried out during his reign, as well as his companions. Since this research is related to the Holy Qur’an and its position with other religions, the appropriate method that the researcher relied on is the inductive and analytical methods. The research concluded that the position of the Holy Qur’an was clear and explicit with other religions on the truth of one principle, which is that the Almighty Allah is the one who created all human beings from male and female, and the best and most pious among people is the one who fears the Almighty Allah. The Holy Qur’an also made an explicit reference to giving other religions freedom of belief, thought, and worship, so that, it did not force them to enter Islam. Thus, the Holy Qur’an addressed the People of the Book with a common word and alerted them to the distortions that had occurred in their books.